Effect of diets low and high in refined sugars on gut transit, bile acid metabolism, and bacterial fermentation. Issue 4 (April 1991) - Kruis, W; Forstmaier, G; Scheurlen, C; Stellaard, F
Abstract : Increasing consumption of refined sugar has been implicated in many gastrointestinal disorders on epidemiological grounds. Nine volunteers agreed to participate in a study comparing the effects of a diet containing 165 g refined sugar/day with a diet of only 60 g/day on gut transit, bile acid metabolism, and fermentative activity of the intestinal flora. The wet and dry weight, pH, and water content of the stools were similar on the two diets. On the high sugar diet mouth-to-anus transit time was significantly prolonged, despite a shortened mouth-to-caecum transit time. The faecal concentration of total bile acids and the faecal concentration of secondary bile acids increased significantly. Diet affected neither the serum bile acid pattern nor the concentration. Breath hydrogen tests showed significantly enhanced H2 production on the high sugar diet. We conclude that the quantity of refined sugar in the diet can significantly influence gut function and the composition of bowel contents.